2014
DOI: 10.5114/pm.2014.45001
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the results of uterine artery embolization: correlation between initial intramural fibroid volume and percentage volume decrease

Abstract: Introduction and objectiveUterine artery embolization (UAE) is a minimally invasive treatment option for symptomatic fibroids. Long-term follow-up studies have shown that at five-year follow-up after UAE, up to 30% of patients required a hysterectomy. Therefore, it seems of utmost importance to identify patients, who are unlikely to benefit from UAE. It has been postulated that the percentage volume reduction of fibroids may predict long-term UAE outcome. The results of available studies are equivocal, therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 24 publications
(46 reference statements)
1
16
4
Order By: Relevance
“…[19] Available literature data show that 3 months after UAE the median percentage reduction of the dominant myoma volume ranged from only 3 up to even 93%, but on an average, it was around 50%. [3536] After 6-month follow-up, a 40%–60% fibroid volume reduction was observed in most studies. In some prospective studies, 3 years after UAE total uterine volume was reduced significantly, on an average up to 65%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Available literature data show that 3 months after UAE the median percentage reduction of the dominant myoma volume ranged from only 3 up to even 93%, but on an average, it was around 50%. [3536] After 6-month follow-up, a 40%–60% fibroid volume reduction was observed in most studies. In some prospective studies, 3 years after UAE total uterine volume was reduced significantly, on an average up to 65%.…”
Section: Discussionmentioning
confidence: 99%
“…[2634] Effects of UAE seem not only to be permanent but also progresses with time. [35] The reported success rate of UAE assessed as the decrease in the largest myoma volume ranges from only 23 to even >90%. [19] Available literature data show that 3 months after UAE the median percentage reduction of the dominant myoma volume ranged from only 3 up to even 93%, but on an average, it was around 50%.…”
Section: Discussionmentioning
confidence: 99%
“…The success of transarterial UAE of fibroids depends on precisely identifying the origin of uterine arteries, along with highly selective catheterization ( 20 ). Previous studies have indicated that excessive embolization may damage normal myometrium, ovaries or fallopian tubes, resulting in uterine necrosis, infections or ovarian failure in rare cases.…”
Section: Discussionmentioning
confidence: 99%
“…During UAE, performed by an interventional radiologist, embolic material is administered to occlude both uterine arteries, which is achieved by introducing a catheter through the femoral artery into the uterine arteries under X-ray supervision. As a result, blood flow is significantly reduced and ischaemia occurs in the tumour, causing necrosis of fibroid cells [4]. The most important benefits of UAE are uterus preservation and surgery avoidance.…”
Section: Introductionmentioning
confidence: 99%